1998
DOI: 10.2466/pms.1998.86.2.383
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Tactual Discrimination of Heights by Blind and Blindfolded Sighted Subjects

Abstract: The ability of blind and blindfolded sighted subjects to discriminate cubes of different heights was measured using the method of constant stimuli. Five male blind and 5 male blindfolded sighted students, ages 22 to 28 years, were subjects. All blind subjects had undergone orientation and mobility training at a school for the blind. The cubes, made of wood, were explored using a long cane. Subjects were presented the standard cube and a comparison cube and required to judge whether the comparison cube height w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1
5

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 7 publications
0
21
1
5
Order By: Relevance
“…The performance of blind subjects is similar to that of sighted subjects in many tasks (Heller, 1989;Heller and Kennedy, 1990;Castiello et al, 1993;Sergio and Scott, 1998;Sunanto and Nakata, 1998;Grant et al, 2000;Heller et al, 2002b;Vanlierde and Wanet-Defalque, 2004). In contrast, other studies reported that blind subjects outperformed sighted subjects under certain conditions (Rossetti et al, 1996;Van Boven et al, 2000;Goldreich and Kanics, 2003;Gaunet and Rossetti, 2006;Alary et al, 2008).…”
Section: Performance Of Blind Versus Blindfolded Normally Sighted Submentioning
confidence: 53%
“…The performance of blind subjects is similar to that of sighted subjects in many tasks (Heller, 1989;Heller and Kennedy, 1990;Castiello et al, 1993;Sergio and Scott, 1998;Sunanto and Nakata, 1998;Grant et al, 2000;Heller et al, 2002b;Vanlierde and Wanet-Defalque, 2004). In contrast, other studies reported that blind subjects outperformed sighted subjects under certain conditions (Rossetti et al, 1996;Van Boven et al, 2000;Goldreich and Kanics, 2003;Gaunet and Rossetti, 2006;Alary et al, 2008).…”
Section: Performance Of Blind Versus Blindfolded Normally Sighted Submentioning
confidence: 53%
“…If the orientation of the object is changed between study and test, this process can be disrupted because there is a mismatch between the perceived object and its stored representation. Blind individuals gain a considerable part of their knowledge of the surrounding environment through haptic information, translating into behaviorally observable advantages (e.g., Afonso, Blum, Katz, Tarroux, Borst, & Denis, 2010; Norman & Bartholomew, 2011; Sunanto & Nakata, 1998; although see Crabtree & Norman, 2014). Presumably, their reliance on haptic cues facilitates the construction of object-centered representations that are stable across spatial transformations, resulting in view-independent performance.…”
Section: Discussionmentioning
confidence: 99%
“…This plasticity cross modal probably helps to improve the tactile perception abilities in blind people 16,25,26 . The characteristic of the plasticity is represented by an alteration in the cortical topography and an increase of the cortical representation in the analysed area, due to an increase in the peripheral afference associated to an adaptive phenomenon of the cortical representation of the organisation 24,27 .…”
Section: Discussionmentioning
confidence: 99%